An Overview on ELT Course Book - Ismit Karim (Program Studi Pendidikan Bahasa Inggris, STKIP Kie Raha Ternate, 2020)
In the practice of teaching and learning, planned teaching material undoubtedly holds a very crucial role. A textbook is the example of the teaching material that has been used for five decades as the manual instruction as well as a source of information in the teaching and learning activity. Merriam-Webster dictionary defines a textbook as